“Evaluación de tres bioinsecticidas entomopatógenos para el control de gusano cogollero (Spodoptera frugiperda) del cultivo de maíz (Zea mays), en condiciones controladas”. - Jaén Mora, Yury Alfredo (2020)
In the economy of Ecuador, the cultivation of corn is of great importance not only because it is a food that is part of the daily diet of the population of the country, but also because it is a source of employment for many families, The use of entomopathogenic microorganisms are used as control agents of Spodoptera frugiperda, very little is known about the appropriate doses and the mortality effects of larvae of this pest in Ecuador. The objective of this work is to evaluate the effects of three entomopathogenic bioinsecticides on cogollero S. frugiperda worm larvae under controlled conditions, with which three entomopathogens Beauveria bassiana, Bacillus thuringiensis and Metarhizium anisopliae were studied in doses of 25, 20 and 15 ccl-1 each. This research was carried out This research was carried out in the microbiology laboratory of the State Technical University of Quevedo (UTEQ), located at Km 1.5 via Quevedo - Santo Domingo, the Randomized Design was used with 3x3 factorial arrangement in 3 repetitions. The results showed that B. bassiana proved to be the most effective with a mortality of 72%, that is, 7 dead larvae under study. while M. anisopliae and B. thuringiensis with 60 and 50%. The most effective dose was for the High dose (25ccl-1) with 7 dead insects, 70% mortality. In the interactions the entomopathogens B. bassiana and M. anisopliae in high doses (25 ccl-1) recorded mortalities of 90 and 70% respectively during the 192 hours that the investigation lasted. Regarding the efficiencies, the highest was B. bassiana in High dose with 89.63%, followed by M. anisopliae with 65.63% respectively. Keywords: Biologic control, Beauveria bassiana, Bacillus thuringiensis, Metarhizium anisopliae.